2017
DOI: 10.1051/0004-6361/201629725
|View full text |Cite
|
Sign up to set email alerts
|

Doubly15N-substituted diazenylium: THz laboratory spectra and fractionation models

Abstract: Context. Isotopic fractionation in dense molecular cores has been suggested as a possible origin of large 14 N/ 15 N ratio variations in solar system materials. While chemical models can explain some observed variations with different fractionation patterns for molecules with -NH or -CN functional groups, they fail to reproduce the observed ratios in diazenylium (N 2 H + ). Aims. Observations of doubly15 N-substituted species could provide important constraints and insights for theoretical chemical models of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Although the carbon fractionation in HCN may not be well understood, chemical models emphasize the caveats of indirect measurements of isotopic ratios. Recent works have suggested that doubly substituted N 2 H + could be a potential direct probe of the nitrogen isotopic ratio (Dore et al 2017). As demonstrated in the present work, observational, theoretical, and modeling efforts must be combined to enable direct, reliable estimates of isotopic ratios.…”
Section: Discussionmentioning
confidence: 83%
“…Although the carbon fractionation in HCN may not be well understood, chemical models emphasize the caveats of indirect measurements of isotopic ratios. Recent works have suggested that doubly substituted N 2 H + could be a potential direct probe of the nitrogen isotopic ratio (Dore et al 2017). As demonstrated in the present work, observational, theoretical, and modeling efforts must be combined to enable direct, reliable estimates of isotopic ratios.…”
Section: Discussionmentioning
confidence: 83%
“…In that scenario, 15 N atoms are released more efficiently through selective photodissociation of 14 N 15 N around the chemical transition from atomic to molecular nitrogen and are converted efficiently to ammonia ice through hydrogenation on grains. Searching for 15 N in 15 N 15 NH + and in the various deuterated substitutes of N 2 H + , 14 N 15 ND + , 15 N 14 ND + and 15 N 15 ND + is possible thanks to detailed spectroscopic studies (Dore et al 2009, 2017) and could help to further constrain the issue.…”
Section: Resultsmentioning
confidence: 99%
“…Mapping of these molecules may also provide insight into fractionation mechanisms. One interesting possibility is that 15 N2H + could be a significant reservoir of 15 N; recent spectroscopic data mean that searches for this molecule are now possible (Dore et al 2017). (solid lines), as compared to the W12 nitrogen reaction network (dashed lines).…”
Section: Discussionmentioning
confidence: 99%